An eight characters introductory system - Neo, Xian Zhen (2016)
In Chinese tradition, the study of the Eight Characters (八字) refers to the reading of one’s character, fate and various life aspects, such as career and health, based on their date of birth and time. It is based on the interaction of metaphysical elements and comprises of complex and precise systems. This traditional practice is increasingly lost on the millennial generation (1980-2000) and is often deemed as superstition. Moreover, the complexity of the Eight Characters system makes it difficult for the millennial generation to comprehend it. As such, this project utilises design to communicate the Eight Characters reading in an accessible and palatable manner for the people of our times.